Communicative Competence as a Factor of Formation of the Readiness for Professional Activities in Future Employees of the Sector of Security and Defense of Ukraine - Valentyna Tyurina; Mykhailo Koziar; Nataliia Malaniuk (Pedagogical Discourse, 2024)
The relevance of the problem of forming the communicative competence of the future police officer as a factor in the formation and development of his readiness for professional activity is substantiated. The significance of the formation of communicative competence for the formation and development of police officers’ readiness for professional activity is revealed. The definitions of the concepts «communicative competence», «readiness for professional activity», «quest-technology», «educational quest», «police quest» are given. The content of the tasks of the «police quest» is revealed as situations that are as close as possible to the real professional activities of police officers.The relevance of the problem of forming the communicative competence of the future police officer as a factor in the formation and development of his readiness for professional activity is substantiated. The feasibility of introducing interactive technologies, in particular the «police quest», into the process of professional training of future police officers with the aim of forming their communicative competence as a basis for the formation of readiness for professional activity has been revealed. It is shown that there is a statistically probable presence of positive dynamics of results according to most indicators in the experimental groups after studying a special course, writing creative and term papers, and participating in practical classes in the form of a «police quest».